2019
DOI: 10.1002/ijc.32285
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy of the AKT kinase inhibits esophageal squamous cell carcinoma growth in vitro and in vivo

Abstract: Esophageal cancer, a leading cause of cancer death worldwide, is associated with abnormal activation of the AKT signaling pathway. Xanthohumol, a prenylated flavonoid tested in clinical trials, is reported to exert anti‐diabetes, anti‐inflammation and anticancer activities. However, the mechanisms underlying its chemopreventive or chemotherapeutic effects remain elusive. In the present study, we found that xanthohumol directly targeted AKT1/2 in esophageal squamous cell carcinoma (ESCC). Xanthohumol significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…To determine whether Xn exerts a potential adjuvant action with chemotherapeutic drugs, we first analyzed its ability to inhibit the proliferation of three CRC cell lines. Some reports have previously described a potential antiproliferative property for Xn that is highly dependent on cell lines, times of treatment, and concentrations of this prenylated chalcone [19,28,29]. For example, Xn at 10 µM inhibited cell proliferation in the thyroid cancer TPC-1 cell line, supporting a potential action against carcinogenesis, while approximately 100 µM Xn decreased cell viability and the main proapoptotic process [30].…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether Xn exerts a potential adjuvant action with chemotherapeutic drugs, we first analyzed its ability to inhibit the proliferation of three CRC cell lines. Some reports have previously described a potential antiproliferative property for Xn that is highly dependent on cell lines, times of treatment, and concentrations of this prenylated chalcone [19,28,29]. For example, Xn at 10 µM inhibited cell proliferation in the thyroid cancer TPC-1 cell line, supporting a potential action against carcinogenesis, while approximately 100 µM Xn decreased cell viability and the main proapoptotic process [30].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, S6K1/pS6 is downstream of the AKT/mTOR pathway, which contributes to the proliferation of esophageal cancer cells, supporting the role of S6K1 in cancer cell proliferation. 36 In addition, liver-specific S6 knockout in mice led to severe cell cycle arrest, indicating the critical role of S6 in cell cycle progression. 37 At present, the direct regulatory mechanism by which ACTL6A regulates the phosphorylation of S6 to control cell cycle regulators remains unclear.…”
mentioning
confidence: 99%
“…Li B et al reported that the AKT pathway were associated with increased cancer cell invasiveness, demonstrating that this pathway may be a valid target in the treatment of metastatic ESCC (Li et al, 2017). The growth of esophageal cancer can be significantly inhibited by targeting the AKT kinase (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%